CONGENITAL CLUBFOOT: ETIOPATHOGENETIC MECHANISMS AND TREATMENT CHALLENGES - Milanović, Filip (Medicinski podmladak, 2024)
Clubfoot is recognized as one of the most frequent musculoskeletal deformities. Being characterized by ankle equinus, hindfoot varus, forefoot adduction, cavus and calf muscles’ atrophy, it occurs in 1 to 2 per 1000 newborns. The concrete etiology of the deformity is not completely known but different studies suggest multifactorial pathogenesis, including numerous genetic and environmental risk factors. The most frequent clubfoot clinical presentation is isolated while it may also be associated with other neurologic conditions as the part of a syndrome. The disease is easy seen at birth and its degree may vary from mild to an extremely rigid foot that is not reducible to manipulation. The challenge of identifyng the best clubfoot treatment method has become less demanding as Ponseti invented his method that is today thought to be the gold standard, including weekly stretching and casting while following tenotomy of the Achilles tendon is mandatory for rigid equinus. Foot abduction brace treatment for four to five years is indicated in order to prevent relapse. Surgical soft-tissue releases might be necessary for those resistant clubfeet, where conservative treatment is not suffucient. If untreated, clubfoot leads to lifelong disability so it is essentially important to aware parents about the importance of persistent and patient commitment and compliance during the treatment period.The aim of this paper is to show the significance of multifactorial clubfoot etiology as well as different clubfoot therapeutic modalities.
Keywords: clubfoot deformity; clubfoot etiology; Ponseti method; Achilles tenotomy